2017
DOI: 10.1080/09640568.2017.1342612
|View full text |Cite
|
Sign up to set email alerts
|

The missing pillar: Eudemonic values in the justification of nature conservation

Abstract: The public justification for nature conservation currently rests on two pillars: hedonic (instrumental) values, and moral values. Yet, these representations appear to do little motivational work in practice; biodiversity continues to decline, and biodiversity policies face a wide implementation gap. In seven EU countries, we studied why people act for nature beyond professional obligations. We explore the motivations of 105 committed actors for nature in detail using life-history interviews, and trace these ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 48 publications
3
39
0
4
Order By: Relevance
“…In our study, we expected a positive correlation between RV and the appreciation items and between RV and the preservation items because all three are potential motivators for people to conserve nature (Wiseman and Bogner, 2003;Van den Born et al, 2017;Bogner, 2018). The calculated Pearson correlation coefficient between RVs and appreciation for nature almost showed a high effect (r = 0.469).…”
Section: Convergent and Discriminant Validitymentioning
confidence: 77%
“…In our study, we expected a positive correlation between RV and the appreciation items and between RV and the preservation items because all three are potential motivators for people to conserve nature (Wiseman and Bogner, 2003;Van den Born et al, 2017;Bogner, 2018). The calculated Pearson correlation coefficient between RVs and appreciation for nature almost showed a high effect (r = 0.469).…”
Section: Convergent and Discriminant Validitymentioning
confidence: 77%
“…Studies examining the motives behind proenvironmental behavior are common within the conservation literature (Kabii & Horowitz ), where motives are often categorized as either values‐driven or incentive‐based (van den Born et al. ). For example, volunteers in an invasive plant species removal program reported that caring for nature and expressing their values were among their top motives (Pagès et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, van den Born et al. () found that committed conservation actors are driven by their belief that nature contributes to a meaningful life. Similar motives have been demonstrated in participants in an invasive plant species eradication program (Pagès et al.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar vein, moral obligations towards non-human nature, based on an extended range of similarities to human attributes, remain implicitly anthropocentric through their reliance on the demonstration of specific cognitive or sentient capacities (see Benton, 1993). Yet at the same time, most modern legal frameworks, including many international statutes, indulge in a form of ironic or unintended animism through the recognition of rights for institutional entities such as corporations and other inanimate "things" (see Tavares, 2014).…”
Section: Loving the Alienmentioning
confidence: 99%